The Trend of CEACAM3 Blood Expression as Number Index of the CTCs in the Colorectal Cancer Perioperative Course. (18th October 2015) - Taddei, A.; Castiglione, F.; Ringressi, M. N.; Niccolai, E.; Tofani, L.; Boni, L.; Bechi, P.; Amedei, A.
Abstract : Pathological stage seems to be the major determinant of postoperative prognosis of solid tumors, but additional prognostic determinants need to be better investigated. The most important tumor marker for colorectal cancer (CRC) is the cell-surface antigen, Carcinoembryonic Antigen (CEA), and its assessment is considered a valuable index of circulating tumor cells (CTCs). In this paper, CEACAM3 evaluation was applied given its great specificity in the CRC. Whole blood from the basilic vein of 38 CRC patients was collected before and at various time intervals after the curative resection. Also, from 20 of them, we have obtained two additional intraoperative samples. CEACAM3 expression was evaluated in all the samples by RT-PCR. CEACAM3 duct values showed a decreasing trend from preoperative through early and later postoperative to 6th-month samples (p < 0.001 ). The average values of CEACAM3 were related to the cancer size (T stage) (p = 0.034 ) and WHO stage (p = 0.035 ). A significant effect of the baseline value of CEACAM3 dCt on the temporal trend has been observed (p < 0.001 ). In this study, we have demonstrated the CEACAM3 specificity and a perioperative trend of CTCs which is coherent with the clinical/pathological considerations and with previous experimental findings in different cancer types.